2012
DOI: 10.1002/jclp.21952
|View full text |Cite
|
Sign up to set email alerts
|

First‐Generation Student Veterans: Implications of Poverty for Psychotherapy

Abstract: Student veterans are arriving at university and college campuses and many counselors may not be prepared. Multiple and intersecting identities complicate the student's integration and matriculation into higher education. We review literature on first-generation college students and issues pertinent to student veterans. Using the revised Social Class Worldview Model, this article offers a case example to illustrate how counselors may best work with student veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…To address the need for these services, campuses are providing either (a) on-campus counseling services for SSM/Vs and their families or (b) assistance in finding appropriate services (Cook & Kim, 2009; Danish & Antonides, 2009). Institutions with larger SSM/V populations are more likely to train staff on working with military issues (see Wurster, Rinaldi, Woods, & Liu, 2013). Approximately 84% of campuses provide assistance for PTSD, 55% provide assistance with physical disabilities, and 35% assist with brain injuries (McBain et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…To address the need for these services, campuses are providing either (a) on-campus counseling services for SSM/Vs and their families or (b) assistance in finding appropriate services (Cook & Kim, 2009; Danish & Antonides, 2009). Institutions with larger SSM/V populations are more likely to train staff on working with military issues (see Wurster, Rinaldi, Woods, & Liu, 2013). Approximately 84% of campuses provide assistance for PTSD, 55% provide assistance with physical disabilities, and 35% assist with brain injuries (McBain et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…According to recent reports, returning veterans can face complex challenges when pursuing their degrees Griffin & Gilbert, 2012;Minnis, Bondi, & Rumann, 2013;Rudd, Goulding, & Bryan, 2011). These can include finding the help they need both on campus and in the S60 SELBER, CHAVKIN, BIGGS community, understanding their new roles as students and their options for new careers, navigating the campus bureaucracy, developing relationships with campus faculty and students who may not understand their past military experiences, and academic challenges such as potential learning disabilities and re-engaging with academics after years of service (Griffin & Gilbert, 2012;Wurster, Rinaldi, Woods, & Liu, 2013). Many universities are not equipped to understand the student veteran's needs or to develop the services needed to fill these gaps, leaving the student veteran with few tools to make the transition (National Association of Student Affairs Personnel and Administrators, 2013).…”
Section: The Veterans Initiative Model: Serving Student Veteransmentioning
confidence: 99%
“…Attention has been given to the function of objective indices of social class and other demographic variables on veterans and first-generation students educational achievement and well-being (Institute of Medicine, 2013;Pascarella, Pierson, Wolniak, & Terenzini, 2004), while less attention has been given to the function of subjective social class on these populations. Subjective social class is argued here to be a critical part of these groups' identities which influences their performance and well-being in college (Wurster et al, 2013). Social class is a salient factor for these individuals as they come from families with differing financial, human, social, and cultural capital, compared to many continuing generation students.…”
Section: List Of Tablesmentioning
confidence: 90%
“…Many of these individuals (62-66%) are first-generation students (National Survey of Student Engagement, 2010; U.S. Department of Veterans Affairs, 2014). As both veterans and first-generation students face multiple barriers to college success (Stephens, Fryberg, Markus, Johnson, & Covarrubias, 2012), it has been suggested that individuals with this intersecting identity are at even greater risk for attrition (Wurster, Rinaldi, Woods, & Liu, 2013). However, to date, there have been no studies on first-generation college student veterans.…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation